The persistence of Cambodian poverty from the killing fields to today - Kerbo, Harold R. (McFarland & Co., 2011)
"This book includes a short history of Cambodia and covers the systemic nature of Cambodian poverty, the economic success stories of Vietnam and Laos, the corruption in Cambodia, and hopes for its future. Intended for the general reader, this book is particularly relevant to those interested in the broader issue of eliminating world poverty"--Provided by publisher.